Harmonization of Malaysian laws with Islamic laws on elimination of child labour across the nation - Yusuff Jelili, Amuda; Nik Ahmad, Kamal; Ashgar Ali, Ali Muhamed; Azizah, Mohd; Marhanum, Che Mohd Salleh (2016)
Some Malaysian children are working for different reasons. This study discuses harmonisation of Malaysian laws on child labour to protect children from hazardous labour. Child labour is a global problem due to poverty, culture, laziness, and corruption, among others. It is the parents' and government duty to provide adequate provisions for the citizens, particularly in childhood. This paper examines the harmonisation of lslamic law, Children and Young Person Employment Act 1966, Education Act 1996, Child Act and United Nations Convention. Many contemporary Muslim jurists strongly maintain their position that civil laws or common laws are un-Islamic while the majority of man-made laws argued that lslamic fiqh is unsuitable for the contemporary life of Muslims and new issues globally. If the man-made laws or United Nations Conventions on the elimination of child labour are in line with the Qur'an and hadith as well not contravening the principles of the Islamic law, then the provisions are permissible.